Evidence that perceptions of and tolerance for medical ambiguity are distinct constructs: An analysis of nationally representative US data. - Simonovic, Nicolle; Taber, Jennifer M.; Klein, William M. P.; Ferrer, Rebecca A. (Health Expectations, 2020)
Background: Medical information is often conflicting and consequently perceived as ambiguous. There are individual differences both in how much people perceive ambiguity and in their tolerance for such ambiguity. Little is known about how these constructs are related to each other and with other beliefs. Objective: To examine the association between (a) perceived medical ambiguity, (b) tolerance for medical ambiguity and (c) their associations with various medical and cancer‐specific judgement and decision‐making correlates. Method and Participants: We conducted secondary data analyses using the cross‐sectional, nationally representative Health Information National Trends Survey 4, Cycle 4 (n = 3,433, 51.0% female, Mage = 46.5). Analyses statistically controlled for age, sex, race, education and health‐care coverage. Main variables studied: Perceived medical ambiguity, tolerance for medical ambiguity, cancer perceptions, health‐care experiences and preferences, and information‐seeking styles and beliefs. Results: Perceived medical ambiguity and tolerance for medical ambiguity were statistically independent. Higher perceived ambiguity was associated with lower perceived cancer preventability, lower reliance on doctors, lower perceived health and information‐seeking self‐efficacy, lower perceived quality of the cancer information‐seeking process, and greater cancer information avoidance. Lower tolerance for ambiguity was associated with lower cancer worry, lower trust in doctors, lower likelihood of seeking health information, and lower engagement in medical research. Discussion and Conclusions: Perceived medical ambiguity and tolerance for medical ambiguity seem to be distinct constructs. Findings have implications for how people make medical decisions when they perceive and prefer to avoid conflicting medical information.